Konsep Tazkiyah Al-Nafs dalam Al-Qur’an dan Implikasinya Terhadap Pendidikan Agama Islam - Aprilia, Nindy Putri; Surahman, Cucu; Sumarna, Elan (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This research aims to explore the concept of tazkiyah in the Al-Qur'an and its implications for education, especially Islamic Religious Education. This research uses library research and literature review methods, which aim to collect information and data from various sources such as books, articles and relevant journals. Data analysis was carried out using thematic analysis techniques to identify patterns and themes that emerged from the literature studied. The results of the research reveal in the Al-Qur'an Surah As-Syams verses 9-10,